해양경찰청 전문수사관 운영제도의 개선방안에 관한 연구 - 손영태 (한국해양경찰학회보, 9(2), 2019)
해양경찰의 주요역할 중 “수사” 기능은 국민의 신체 자유와 재산을 박탈하는 형사제재 수단임과 동시에 국가권력 작용으로 반드시 법률과 적법한 절차를 따르도록하고 있으며, 수사과정에서 수집된 증거능력에 대해서도 엄격한 기준이 적용된다. 이에 따라 해양경찰청에서는 해양경찰의 특화된 전문분야의 수사역량을 강화하고공판중심주의에 따른 사법환경 변화에 선제적으로 대응하기 위한 조치로 수사 분야별 일정한 자격 요건을 갖춘 사람(도입 당시는 “수사경찰관”으로 표기)을 대상으로한 전문수사관 인증제도를 2012년 7월에 도입하여 현재까지 운영하고 있다. 하지만 전문수사관의 자격요건은 근무경력, 근무실적 및 교육이수 등 주로 실무경력과 최소한의 평가·심사 과정만을 요구하고 있어 실질적인 실무역량을 평가하기 위한 요소를 갖추고 있지 못하며, 또한 이는 해양을 배경으로 다양한 분야에서 발생하고 있는 각종 사건·사고를 전문적으로 처리하는데 있어서의 제한적 조치에 따른 한계가 있으므로 이를 해결하기 위한 제도적 정비가 필요할 것으로 보인다. 따라서 본 논문에서는 갈수록 진화하는 해양범죄 및 현 사법체계에 대응하기 위한 조치로 수사 전문성 강화 및 전문수사관을 체계적으로 지원·관리할 수 있는 방안을 마련하여 해양경찰 수사의 발전적 기반 조성에 필요한 대안을 제시하고자 한다. Among the major roles of Korea Coast Guard(KCG), the "investigation" function is the meaning of criminal sanctions at the same time state authority actions that deprive people‘s physical freedom and property. While also requiring them to follow Act and through lawful procedures, and strict standards are applied to the evidence capabilities collected during the investigation process. Accordingly, KCG introduced and operated a professional investigator certification system in July 2012 for those who have certain qualifications to the fields of investigations(referred to as "investigation police officers" at the time of the introduction) in a move to strengthen the investigation capabilities of specialized fields of maritime police and as a measure to preemptively respond to changes in the judicial environment caused by Trial-Centralism. However, the qualifications of professional investigators are not equipped with elements for assessing actual duties capabilities, mainly because they require only the practical experience and minimal evaluation and examine proceedings, such as work experience, work performance, and education completion, and this is also due to the limitations of limited measures in professional handling of various cases and accidents occurring in several fields against the backdrop of the sea, which will require system readjustment to solve them. Therefore, this article would like to establish investigation professionalism to reinforcement measures and systematically support and management professional investigator certification system improvement and to present alternatives necessary for the creation of the foundation for the development of KCG investigations, in order to respond gradually evolving maritime crimes and the current judicial system. KCI Citation Count: 1